1992
DOI: 10.1042/bj2880675
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that GLUT-2 mRNA and protein concentrations are decreased by hyperinsulinaemia and increased by hyperglycaemia in liver of diabetic rats

Abstract: GLUT-2, glucokinase (GK) and phosphoenolpyruvate carboxykinase (PEPCK) mRNA expression was studied in the liver of chronically catheterized diabetic rats during the 3 days after an intravenous injection of 65 mg of streptozotocin (STZ)/kg. At 6 h after the STZ injection, portal plasma insulin levels were 270 +/- 32 mu-units/ml and blood glucose was 1.4 +/- 0.4 mmol/l, owing to pancreatic beta-cell destruction. GLUT-2 and PEPCK mRNA concentrations were rapidly and dramatically decreased (> 90%), whereas GK mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 33 publications
5
55
1
Order By: Relevance
“…Also, liver GLUT2 expression in rats is reduced during starvation and increases to normal levels after refeeding [41]. In diabetic rats, liver GLUT2 expression is increased, but is corrected to regular levels when exogenous insulin returns the hyperglycemic conditions to normal [42]. These data suggest that GLUT2 expression in the liver is stimulated by glucose and downregulated by insulin.…”
Section: Effects On Carbohydrate Metabolismmentioning
confidence: 47%
“…Also, liver GLUT2 expression in rats is reduced during starvation and increases to normal levels after refeeding [41]. In diabetic rats, liver GLUT2 expression is increased, but is corrected to regular levels when exogenous insulin returns the hyperglycemic conditions to normal [42]. These data suggest that GLUT2 expression in the liver is stimulated by glucose and downregulated by insulin.…”
Section: Effects On Carbohydrate Metabolismmentioning
confidence: 47%
“…In the only previous study that examined GLUT2 in liver of type 2 diabetic subjects, GLUT2 transporter protein was found to be increased approximately twofold compared with lean nondiabetic control subjects (32). Because hyperglycemia has been found to upregulate GLUT2 in animal models of diabetes (33), one could argue that the magnitude of the increase in GLUT2 protein described by Burguera et al (32) was inappropriate. Nonetheless, when viewed in absolute terms, in the only study in which it was measured, hepatic GLUT2 protein was found to be increased in type 2 diabetic patients compared with lean nondiabetic control subjects.…”
Section: Discussionmentioning
confidence: 72%
“…Consistent with this scenario, we found a positive correlation between decreased SGU and the HbA 1c , suggesting that poor glycemic control may sensitize the liver to the inhibitory effect of elevated plasma FFA levels. With regard to this, animal studies have shown that hyperglycemia impairs hepatic glucokinase activity (33,38). Furthermore, it is possible that if the present study was performed at each subject's elevated fasting plasma glucose concentration (i.e., without an overnight insulin infusion), an even greater FFA-induced inhibition of SGU may have been observed.…”
Section: Discussionmentioning
confidence: 95%
“…The expression of the genes for several other proteins is regulated by glucose; these include genes for L-type pyruvate kinase (13,14), fatty-acid synthase (15,16), PEPCK (17,18), and the type 2 glucose transporter (GLUT-2) (19,20). The mechanism by which glucose regulates the expression of these genes remains largely unknown.…”
Section: From the Department Of Nutrition Case Western Reserve Univementioning
confidence: 99%
“…Hepatic Glc-6-Pase activity is effectively regulated by hormonal and nutritional status. For example, fasting and hormones that increase cAMP concentration stimulate its gene expression while refeeding and insulin decrease it (1, 2, 6 -12).The expression of the genes for several other proteins is regulated by glucose; these include genes for L-type pyruvate kinase (13, 14), fatty-acid synthase (15, 16), PEPCK (17, 18), and the type 2 glucose transporter (GLUT-2) (19,20). The mechanism by which glucose regulates the expression of these genes remains largely unknown.…”
mentioning
confidence: 99%